Introduction to cataracts of the eye - Badakere, Akshay (Henry Stewart Talks, 2023)
Definition and causes of cataracts, Embryology and anatomy of the lens, Classification of cataracts, Cataracts in adults (types, causes, and mechanisms), Cataracts in children (types, causes, and genetics)